(untitled) (Thobaqot: Jurnal Ilmu Hadis, 2023)
This research was motivated by researchers’ curiosity about the community’s tendency towards several traditions of the Danau Kedap village community who still believe in and respect the traditional heritage of their ancestors. Starting from the tradition of ngantar kembang which is regularly carried out every year. This tradition is carried out when the month of Ramadan approaches, which coincides with when people start to descend from Besawah, and this tradition has been carried out for generations. Therefore, this research aims to find the basis for introducing the ngantar kembang tradition in Danau Kedap village, the implementation process, and the community’s understanding of the ngantar kembang tradition. This research uses qualitative methods which are closely related to the study of living hadith, then researchers collect data through observation, interviews, and documentation. The approach used by researchers in this research is phenomenological. Meanwhile, researchers used qualitative descriptive analysis techniques for data analysis. Based on the findings of this research, the ngantar kembang tradition is based on the hadith of the Prophet, where previously the Prophet prohibited pilgrimages, but now pilgrimages are permitted because they can remind you of death. There are three processions in ngantar kembang, the first is praying (tahlil) on the road, the second is the khatam al-Qur’an and the third is delivering the flowers. Regarding people’s understanding, researchers found that this tradition means remembering death, rejecting evil, and building brotherhood.